Role of Computed Tomography in Blunt Abdominal Trauma - Khadka, Digbijay Bikram; Sharma, Anup; Bhatta, Ashish; Maharjan, Prabir; Sharma, Sandesh (Journal of Nepalgunj Medical College, 2022)
Introduction: Blunt abdominal trauma is one of the commonly encountered surgical emergencies. The diagnostic modality that helps in optimum management of these patients includes chest and abdominal x-rays, Focused Assessment Sonography for Trauma scan and Computed Tomography. In selected hemodynamically stable patients who are candidates for non-operative management, Contrast Enhanced Computed Tomography is not considered essential and hence avoiding its own radiation hazards and decreasing extra financial burden to the patients. Aims: To evaluate whether Contrast Enhanced Computed Tomography is necessary or not in case of blunt trauma abdomen. Methods: This is a hospital based prospective study done in the department of surgery at Nepalgunj Medical College, Kohalpur conducted from October 2020 to March 2021. The patients with blunt abdominal trauma who were hemodynamically stable at the time of presentation and those who became stable after resuscitation were included. These patient’s detailed history was taken, clinical examination done. Focused Assessment Sonography for Trauma scan was done at the time of presentation along with chest x-ray and other necessary blood investigation. Data were analyzed with Statistical Package for Social Sciences version 25 and p-value <0.05 was taken as significant. Results: Out of total 53 patients, age group between 11-20 and 21-30 years comprising of 13 patients with male: female ratio of 1.94:1 were affected more. Fall injury, being the most common mode, comprised 20 patients. The commonest organ involved was spleen seen in 17 patients (32.1%), liver in 16 patients (30.2%). In 44 (83.0%) patients, Computed Tomography scan was done only in nine patients who were also managed conservatively, except one who underwent laparoscopic evacuation of collected blood. Seventeen (32.1%) patients underwent repeat ultrasonography without any new findings. Conclusion: Patients with blunt abdominal trauma with stable hemodynamics can be managed conservatively with limited use of Contrast Enhanced Computed Tomography scan.